Ultrastructural changes in cortical synapses shortly after termination of a seizure during kindling - Langmeier, M; Fischer, J; Mares, J (Physiologia Bohemoslovaca, 1982)
Repeated electrical stimulation of the sensorimotor region of the rat cerebral cortex at 10-min intervals led to progressive lengthening of the self-sustained after-discharges (SSAD). 50-60 s after termination of the third SSAD we examined, in the electron microscope, type I synapses (after Gray) in the second cortical layer of the sensorimotor region of the contralateral hemisphere. In the experimental animals we demonstrated swelling of both the pre- and post-synaptic elements, a decrease in the number of agranular synaptic vesicles and variability of their shape and size. Frequent manifestations of exo- and endocytic activity and a frequent incidence of complex vesicles have been described. Saccular dilatation of the space between the outer and inner mitochondrial membrane in the presynaptic terminal and dilatation of the terminal cisternae and extracellular space occurred. Alteration of the spine apparatus was observed in the postsynaptic elements. At the margin of the active zone we described simultaneous invagination of the pre- and postsynaptic membrane up to the formation of rounded structures with two concentric membranes. The changes in the synapses are conceived as signs of exhaustion due to the previous epileptic seizure, which on the other hand, activated the restitution mechanisms of the structure of the synaptic apparatus.
Keywords: inbrední kmeny potkanů; Rats, Inbred Strains; záchvaty; Rats; Somatosensory Cortex; synapse; motorické korové centrum; somatosenzorické korové centrum; Synaptic Membranes; mužské pohlaví; Synaptic Vesicles; Seizures; krysa rodu Rattus; Motor Cortex; mozková kůra; Kindling, Neurologic; zvířata; synaptické vezikuly; Cerebral Cortex; synaptické membrány; Synapses; kindling; Male; Animals